Is it good or bad to fish with FADs? What are the real impacts of the use of drifting FADs on pelagic marine ecosystems?. Issue 3 (16th May 2012) - Dagorn, Laurent; Holland, Kim N.; Restrepo, Victor; Moreno, Gala
Abstract: The use of fish aggregating devices (FADs) by purse seine fisheries has come under increasing criticism for its potential deleterious impacts on tuna stocks, for high levels of by‐catch and threats to the biodiversity of tropical pelagic ecosystems. Here, we review the current state of scientific knowledge of this fishing technique and current management strategies. Our intent is to encourage objective discussion of the topic and highlight areas worthy of future research. We show that catching juvenile tuna around FADs does not necessarily result in overfishing of stocks, although more selective fishing techniques would likely help obtain higher yield. Levels of non‐tuna by‐catch are comparable to or less than in other commercial tuna fisheries and are primarily comprised of species that are not considered threatened. Accordingly, to minimize impacts on ecosystem balance, there is merit in considering that all species captured in purse seine fisheries (excluding vulnerable species such as turtles and sharks) should be retained, but the consequences of such a measure should be carefully examined before implementation. The take of vulnerable species could be further reduced by introduction of additional mitigation measures, but their potential benefits would be limited without parallel efforts with other gears. Finally, there is no unequivocal empirical evidence that FADs represent an 'ecological trap' that inherently disrupts tuna biology although further research should focus on this issue. We encourage RFMOs to expand and improve their FAD management plans. Under appropriate management regimes, FAD fishing could be an ecologically and economically sensible fishing method.